2011
DOI: 10.1021/jo102385u
|View full text |Cite
|
Sign up to set email alerts
|

(N-Heterocyclic Carbene)-Pd-Catalyzed Anaerobic Oxidation of Secondary Alcohols and Domino Oxidation−Arylation Reactions

Abstract: The use of commercially available (SIPr)Pd(cinnamyl)Cl (SIPr = 1,3-bis(2,6-diisopropylphenyl)-4,5-dihydroimidazol-2-ylidene) as a precatalyst for the anaerobic oxidation of secondary alcohols is described. The use of this complex allows for a drastic reduction in the reaction times and catalyst loading when compared to the unsaturated counterpart. This catalytic system is compatible with the use of microwave dielectric heating, decreasing even further catalyst loading and reaction times. Domino Pd-catalyzed ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2011
2011
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(23 citation statements)
references
References 34 publications
1
22
0
Order By: Relevance
“…The electron-rich benzylic alcohols could be oxidized smoothly to give the desired products in high yields (Table 2, entries 7, 8 and entries 12e14). On the other hand, the benzyl alcohols with electron-withdrawing groups gave lower yields (Table 2, entries 9, 10 and entries 15,16). Increasing the reaction time did not improve the yield (Table 2, entry 17).…”
Section: Oxidation Of Alcohols Catalyzed By Pd (Ii)mentioning
confidence: 98%
See 1 more Smart Citation
“…The electron-rich benzylic alcohols could be oxidized smoothly to give the desired products in high yields (Table 2, entries 7, 8 and entries 12e14). On the other hand, the benzyl alcohols with electron-withdrawing groups gave lower yields (Table 2, entries 9, 10 and entries 15,16). Increasing the reaction time did not improve the yield (Table 2, entry 17).…”
Section: Oxidation Of Alcohols Catalyzed By Pd (Ii)mentioning
confidence: 98%
“…A number of N,Oligands delivered high TOFs for the palladium-catalyzed oxidation of aliphatic alcohols [14]. Navarro et al reported the use of (NHC)-Pd (N-Heterocyclic Carbene)-catalyzed anaerobic secondary alcohol oxidation with short reaction time and low palladium loading [15]. It has been well-known that ligated Pd (II) complexes can undergo direct dioxygen-coupled catalytic turnover without cocatalysts for oxidation reaction.…”
Section: Introductionmentioning
confidence: 99%
“…Domino Pd-catalysed synthesis of α-arylated ketones from secondary aryl alcohols in very good yields was also reported. 140 Selective oxidations of benzylic and aliphatic alcohols to aldehydes and esters, by O 2 in the presence of the ligand α,α -bis(di-t-butyl phosphino)-o-xylene or Bu n P(1adamantyl) 2 and the additive AgPF 6 in toluene and in the presence of various alcohols, were achieved using Pd(OAc) 2 as the catalyst without the need for additional organic hydrogen acceptors. 141 In a parallel study, the [PdCl 2 (MeCN) 2 ]-catalysed esterification of benzylic alcohols with methanol and various long-chain aliphatic alcohols in the Organic Reaction Mechanisms 2011…”
Section: N Fementioning
confidence: 99%
“…Over the past few years they have gradually replaced the conventional phosphane ligands. The transition-metal complexes of these versatile ligands have been shown to be excellent catalysts for various organic transformations [914]. Among the various NHCs 1,3-diarylimidazolylidenes are the most widely studied systems [1214].…”
Section: Introductionmentioning
confidence: 99%
“…The transition-metal complexes of these versatile ligands have been shown to be excellent catalysts for various organic transformations [914]. Among the various NHCs 1,3-diarylimidazolylidenes are the most widely studied systems [1214]. In the past five years 1,2,3-triazol-5-ylidenes have emerged as promising ligands for transition-metal chemistry [1520].…”
Section: Introductionmentioning
confidence: 99%